Effector Cytokine Profiles of Ex Vivo Expanded CTLs in Colorectal Cancer HCT-116 Cells Co-Culture Models - Ibrahim, Sugeng; Putra, Agung; Hidayah, Nurul; Cahyani, Dini (Indonesian Journal of Medical and Pharmaceutical Science, 2025)
Background: Colorectal cancer (CRC) remains a major cause of cancer-related mortality worldwide, with limited benefit from conventional therapies in advanced disease. Cytotoxic T lymphocytes (CTLs, CD8⁺ T cells) are critical mediators of anti-tumor immunity, primarily through direct cytotoxicity and cytokine secretion. However, the dual roles of CTL-derived cytokines, particularly interferon-γ (IFN-γ), tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6), in CRC progression remain incompletely understood. This study aims to analyze the cytokine profile (IFN-γ, TNF-α, and IL-6) in a CTL–CRC cell direct co-culture model. Methods: CD8⁺ T cells were isolated from peripheral blood mononuclear cells (PBMCs) of CRC patients using magnetic negative selection and activated for 5 days with anti-CD3/CD28 beads and IL-2. Purity and viability were assessed by flow cytometry and morphology. Activated CTLs were co-cultured with the HCT116 CRC cell line at effector-to-target (E:T) ratios of 1:1, 5:1, and 10:1 under direct contact for 48 h. Supernatants were collected and cytokine levels (IFN-γ, TNF-α, and IL-6) were quantified using validated sandwich ELISA kits. Results: Direct co-culture with HCT116 cells significantly increased cytokine secretion in an E:T ratio-dependent manner. IFN-γ secretion rose from 3044.6±120 pg/mL at 1:1 to 4882.1±198 pg/mL at 5:1, plateauing thereafter. TNF-α levels remained relatively constant (628.6±67 pg/mL at 1:1 vs. 674.0±91 pg/mL at 10:1). IL-6, nearly undetectable at 1:1 (0.4±0.1 pg/mL), increased dose-dependently to 5.1±0.9 pg/mL at 10:1. Conclusion: Ex vivo expanded CTLs from CRC patients exhibit a distinct cytokine secretion profile characterized by robust IFN-γ release, stable TNF-α production, and a dose-dependent increase in IL-6 across different effector-to-target ratios.